Macroeconomic impacts of external shocks and anti-shock policies in Bolivia: a CGE analysis - Luis Carlos Jemio M.; Manfred Wiebelt (Kiel Institute of World Economics (IfW), 2002)
Bolivia's mid-term growth prospects are promising but these prospects could be lost, due to social unrest and political instability, if the country does not solve its short-term economic problems, resulting from both external shocks and internal factors. Against this background, this paper analyzes whether the Bolivian economy has any possibility at all to apply anti-shock policies in order to cushion the short-term effects of shocks. For this purpose, a recursive-dynamic CGE model is described which includes both real and financial sectors and which captures the particular features that characterize the functioning of the Bolivian economy. The model is then used to evaluate the effects of external shocks and to test the effectiveness of different policies.
Keywords: O54; E63; C68; 330; CGE model; Bolivia; macroeconomic adjustment; Wirtschaftliche Anpassung; Schock; Allgemeines Gleichgewicht; Dynamisches Modell; Wechselkurspolitik; Finanzpolitik; Schuldenerlass; Wirtschaftspolitische Wirkungsanalyse; Bolivien